Efficacy and Safety of Intraperitoneal Local Anesthetics in Laparoscopic Appendectomy: A Systematic Review and Meta-Analysis. (2nd January 2020) - Abdelhakim, Ahmed Mohamed; Elghazaly, Shrouk M.; Lotfy, Ahmed
Abstract: Intraperitoneal local anesthetics have been increasingly used nowadays. However, they are not routinely given in laparoscopic appendectomy and a lot of controversies are found about their administration in this procedure. The goal of this study is to review effectiveness and safety of intraperitoneal local anesthetics in laparoscopic appendectomy. We conducted a computer search of four authentic databases. We included randomized controlled trials (RCTs) which compared intraperitoneal local anesthetics versus control group in laparoscopic appendectomy. Data were extracted from eligible studies and pooled in a meta-analysis model using RevMan software. We evaluated post-operative pain in different periods and safety outcomes including postoperative nausea and vomiting (PONV) and shoulder pain. Furthermore, we assessed the length of hospital stay and postoperative opioid consumption within 24 hours. Seven RCTs were included with a total of 579 patients in this review. Our analysis indicated a significant difference in postoperative pain at different durations preferring intraperitoneal local anesthetics compared to control. Moreover, intraperitoneal local anesthetics were significantly linked to fewer patients experienced PONV and shoulder pain respectively (RR= 0.28, 95% CI [0.16, 0.50], p < 0.0001), (RR= 0.32, 95% CI [0.17, 0.58], p = 0.0002). We found less hospital stay duration in intraperitoneal local anesthetics group after removal of the heterogeneity (MD= −0.39, 95% CI [−0.63, −0.16], p = 0.001). Intraperitoneal local anesthetics were significantly linked to less postoperative opioid consumption (SMD = −0.60, 95% CI [−0.96, −0.24], p = 0.001). Intraperitoneal local anesthetics can be routinely used in laparoscopic appendectomy as it is associated with less postoperative pain and reduction in different adverse events postoperatively.